Three-step Reduction Therapy of Integrated Chinese and Western Medicine for Thoracolumbar Burst Fracture. Issue 6 (18th August 2019) - Decheng, Wang; Hao, Shi; Zhongwei, Wang; Jiaming, Li; Bin, Yang; Yong, Hai
ABSTRACT: Objective: To investigate and compare the efficacy of three-step reduction (TSR) therapy of integrated Chinese and Western Medicine and posterior open (PO) surgery for thoracolumbar burst fracture. Methods: We selected 60 patients diagnosed with thoracolumbar burst fracture and received treatment in our hospital from December 2014 to March 2017. According to randomized digital table, they were randomly divided into TSR and PO groups. VAS pain grade, Oswestry disability index, height of centrum front, Cobb's angle of spine, bleeding, and complication of internal fixation of the two groups were compared. Results: Postoperative reduction of injured centrum, regained volume of canalis vertebralis, volume of bleeding, and early functional rehabilitation of TSR group were better than that of PO groups ( P < 0.05). Conclusion: Through three-step reduction combined pedicle screw fixation surgery, we can achieve satisfied reduction of thoracolumbar burst fracture, rebuild the height of centrum, recover the biomechanics function of spine, and reduce bleeding. Three-step reduction therapy is an effective therapy for thoracolumbar burst fracture.